Identifying the Effects of the Americans with Disabilities Act Using State-Law Variation: Preliminary Evidence on Educational Participation Effects - Jolls, Christine (American Economic Review, 2004)
Identifying the Effects of the Americans with Disabilities Act Using State-Law Variation: Preliminary Evidence on Educational Participation Effects by Christine Jolls. Published in volume 94, issue 2, pages 447-453 of American Economic Review, May 2004